Estudo experimental da formação e crescimento de hidratos de tetrahidrofurano em uma célula cilíndrica - Mühlstedt, Guilherme (2017)
In the search of becoming self-sufficient in petroleum production, Brazil expanded its offshore technology and recently has began to explore the Pre-salt region. However, the exploration of these fields presents major challenges. In the presalt reserves as well as in diverse fields of exploration around the world, the oil and gas industry must worry about the formation of hydrates during the process of extraction and transportation of its product. The problems in flow assurance related with the hydrates have been addressed by the implementation of hydrate prevention strategies, in other words, by injection of inhibitors, water withdrawal from the system and thermal insulation of lines. However, these methods raise the cost of production, leading industries to apply hydrate management, where there may be hydrate dispersed in the fluid. Nevertheless, the extraction operation has fluctuations and sometimes unexpected stops. These facts can result in the deposition of hydrates in the wall of the pipes, causing partial or total blockages of the line. The present work experimentally studies the annular growth of a hydrate layer, from the wall to the center, using a static cylindrical cell. The experiment used a solution of 1:17 mol of THF in water, the same molar ratio of the formed hydrate, in this way, the growth rate of the hydrate layer is controlled predominantly by the mass transfer phenomenon. This dissertation presents the hydrate layer growth rate for several sub-cooling rates, also presents some observations regarding the morphology of the hydrate under the influence of the temperature in which the experiment was exposed.